2016
DOI: 10.1080/02786826.2016.1152350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relative humidity and particle and surface properties on particle resuspension rates

Abstract: Wind tunnel experiments examined the coupled effects of relative humidity (RH) and surface and particle properties on aerodynamically induced resuspension. Hydrophilic glass spheres and hydrophobic polyethylene spheres »20 mm in diameter, with nanoscale surface features, were resuspended from hydrophilic glass, hydrophobic chemical agent resistant coating (CARC), and gold surfaces. Roughness of the glass and gold surfaces was on the nanoscale, whereas CARC surfaces had microscale roughness. Different particle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…Several wind tunnel studies have assessed the dependency of U th * on the size, density, and shape of dry, non-volcanic particles 15 – 17 , 21 25 . Environmental humidity and moisture content of the deposit also play a role, as demonstrated by studies on wet, non-volcanic particles showing that the presence of water increases inter-particle cohesion, making particles less prone to resuspension 26 29 . Wind tunnel studies on volcanic particles are very limited and the effect of humidity had not been parameterised.…”
Section: Introductionmentioning
confidence: 99%
“…Several wind tunnel studies have assessed the dependency of U th * on the size, density, and shape of dry, non-volcanic particles 15 – 17 , 21 25 . Environmental humidity and moisture content of the deposit also play a role, as demonstrated by studies on wet, non-volcanic particles showing that the presence of water increases inter-particle cohesion, making particles less prone to resuspension 26 29 . Wind tunnel studies on volcanic particles are very limited and the effect of humidity had not been parameterised.…”
Section: Introductionmentioning
confidence: 99%
“…Our study determined the amount of reaerosolization of spores on glass surfaces which are smoother and more hydrophilic compared to other surfaces such as tile and concrete. The average surface roughness for glass is 6.2 nm and the water contact angle is 10.6 (Kim et al 2016). Studies support the notion that adhesive forces are the major determinant in predicting reaerosolization and have shown that there is less reaerosolization of particles deposited from slurries compared to dry deposition methods (Layshock et al 2012).…”
Section: Discussionmentioning
confidence: 59%
“…Higher RH conditions increase water condensation and water contact between a particle and surface, resulting in reduced reaerosolization. A critical RH level, which depends on the particle and surface properties, is required for capillary forces to be observed, and below this RH condition the adhesive force is not affected (Hubbard et al 2012;Kim et al 2016). Hydrophobic particles on hydrophobic surfaces were affected the least by increasing RH conditions; on the other hand, hydrophilic particles on hydrophilic surfaces were affected the most (Kim et al 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations